2022
DOI: 10.3390/dj10120232
|View full text |Cite
|
Sign up to set email alerts
|

Oral Side Effects in Patients with Metastatic Renal Cell Carcinoma Receiving the Antiangiogenic Agent Pazopanib—Report of Three Cases

Abstract: Pazopanib is a potent multi-kinase inhibitor that hinders angiogenesis and blocks tumor growth. It has been approved for the treatment of metastatic renal cell carcinoma (mRCC) and advanced soft tissue sarcoma. There is emerging evidence that bleeding is a common adverse effect of pazopanib and other targeted therapies in patients with mRCC. In addition, jaw osteonecrosis related to pazopanib was recently described in the literature. We report three cases of patients with mRCC who developed adverse oral events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…One case report had reported the occurrence of trismus in an elderly patient after 5 years of commencing first line Sunitinib treatment for metastatic renal cell carcinoma, that also recurred when changing to Pazopanib, and resolved completely upon pazopanib cessation [ 14 ]. A recent publication reported three cases of oral toxicities including two cases of jaw osteonecrosis and one case of gingival bleeding in patients treated with Pazopanib as monotherapy for metastatic RCC [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…One case report had reported the occurrence of trismus in an elderly patient after 5 years of commencing first line Sunitinib treatment for metastatic renal cell carcinoma, that also recurred when changing to Pazopanib, and resolved completely upon pazopanib cessation [ 14 ]. A recent publication reported three cases of oral toxicities including two cases of jaw osteonecrosis and one case of gingival bleeding in patients treated with Pazopanib as monotherapy for metastatic RCC [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pazopanib is a multi-kinase inhibitor, effectively blocking angiogenesis and obstructing tumor expansion. Papadopoulou et al [58] described three patients, aged 64, 63, and 56 years, who developed ONJ following pazopanib therapy for RCC. The treatment regimen for these patients included antibiotics and mouth rinses with 0.2% chlorhexidine.…”
Section: Other Tkismentioning
confidence: 99%
“…Medication-related ONJ (MRONJ) is a multifactorial disease [1,2], occurring especially in the jaws, often at teeth extraction sites, in patients exposed to anti-resorptive drugs (ARDs) [3,4], and in a smaller measure to cyclin inhibitors and antiangiogenic drugs [5]. Indeed, recently, it has also been found that there is a correlation between MRONJ and antiangiogenic drugs, which induce microcirculation dysfunction, which contributes, in turn, to MRONJ [6,7]. Another risk factor contributing to ONJ onset is represented by the mechanical loading to which jaws are subjected, leading to a high bone turnover rate [8,9].…”
Section: Introductionmentioning
confidence: 99%